Control of Ion Transport by Tmem16a Expressed in Murine Intestine - Kunzelmann, Karl; Centeio, Raquel; Wanitchakool, Podchanart; Cabrita, Inês; Benedetto, Roberta; Saha, Tultul; Hoque, Kazi Mirajul; Schreiber, Rainer (Frontiers in Physiology, 2019)
Cl- secretion by the human and murine intestinal epithelium occurs through the cystic fibrosis transmembrane conductance regulator (cftr). However, the Ca2+ activated Cl- channel Tmem16a was shown to contribute to Cl- secretion, mainly, but not exclusively, as a basolaterally located Cl- channel that controls basolateral Ca2+ signaling, and thus activation of basolateral Ca2+ dependent Sk4 K+ channels. In intestinal goblet cells, Tmem16a was shown to regulated Ca2+ signals required for exocytosis of mucus. Because a recent report denied the existence and functional role of Tmem16a in murine intestine, we reexamined in detail expression of mRNA and protein for Tmem16a in mouse colon. In experiments using short-circuited Ussing chamber and whole cell patch-clamp techniques, we further compared ion transport in wild type colon with that in mice with intestinal epithelial specific knockout of Tmem16a. As reported earlier we fully confirm expression of Tmem16a in colonic epithelial cells and the role of Tmem16a for both Ca2+-dependent and cAMP-regulated ion secretion.